THE SYNERGY OF RELIGIOUS AND SCIENCE LEARNING: IMPLEMENTING THE FIVE-DAY SCHOOL CONCEPT - Diana, Melda; Affandi, Faisal Diana; Salman, Nola Fibriyani Bte (Nurul Jadid University, Paiton Probolinggo, East Java, 2025)
This study aimed to analyze the implementation of the five-day concept in religious and science learning which aimed to create synergy between the two disciplines in supporting the academic development and character of students. The concept of five days in this school integrated religious and science lessons with the aim of strengthening students' understanding of the two fields of science holistically. This research used a qualitative approach with a case study method, with data collection techniques through deep-interviews, observations, and documentation. The results of the study showed that the implementation of the five-day concept had succeeded in creating a balanced learning environment between religious values and scientific knowledge, despite challenges in adjusting the curriculum and teaching approaches. The synergy between religious and science learning in this school had a positive impact on the spiritual and intellectual development of students, as well as fostering a critical and creative attitude in facing life's problems. This research was expected to contribute to the development of a learning model that integrates religious values with scientific knowledge in Islamic schools.